Analisis Pengaruh Perencanaan Dan Pengorganisasian Terhadap Mutu Pelayanan di Puskesmas Mulyorejo Kota Surabaya - Erawati, Erawati; Harumanata, Adiyan Agil Fabriandhika; Arofah, Arofah; Winarsih, Tutik (Innovative: Journal Of Social Science Research, 2024)
This study was conducted to determine the effect of planning and organizing factors on the quality of service of Puskesmas Mulyorejo Surabaya City. The sampling technique in this study used total sampling, namely sampling taken in total by taking a sample of 34 respondents (100%). The analysis technique used in this study is multiple linear regression analysis. The results showed that the factors consisting of planning and organizing have a real influence together (simultaneously) on the quality of service at Puskesmas Mulyorejo Surabaya City. Factors consisting of planning and organizing have a real influence individually (partial) on the quality of service at Puskesmas Mulyorejo Surabaya City. Among the factors consisting of planning and organizing, it turns out that planning has a dominant influence on the quality of service at Puskesmas Mulyorejo Surabaya City, with a partial effect of 53.7%. As input recommendations, suggestions can be given, among others: Conduct regular health checks and preventive health checks to the community and implement a quality improvement program to monitor and improve the quality of health services.